Aligning users' and stakeholders' needs: How incentives can reshape the carsharing market. (September 2022) - Cantelmo, Guido; Amini, Roja Ezzati; Monteiro, Mayara Moraes; Frenkel, Amnon; Lerner, Ofer; Tavory, Sharon Shoshany; Galtzur, Ayelet; Kamargianni, Maria; Shiftan, Yoram; Behrischi, Christiane; Azevedo, Carlos M. Lima; Haustein, Sonja; et al.
Abstract: Carsharing services provide users with a new way of approaching mobility and accessing shared vehicles. Since the initial pilot studies in the early 90s, technological innovations (e.g., advances in mobile technology, increased range of electric cars) and the establishment of new business models (e.g, station-based, free-floating, peer-to-peer, packages by time and/or kilometres) helped branding carsharing as a sustainable yet flexible and personalized mobility alternative. On the other hand, the carsharing market today is extremely scattered, as it can include multiple operators, which are often in competition among each other. While this variety of operators provides the user with a variety of travel options, without proper coordination, this competition can reduce the efficiency of the carsharing market and, in extreme cases, of the entire transportation system. In this context, this paper studies the needs of travellers, local authorities, and carsharing service providers, and analyses how incentives can be used to align their goals. Taking Munich, Copenhagen, and Tel Aviv-Yafo as case studies, focus groups were used to identify thirteen different travellers' needs, which are grouped into five main categories: ownership issues, coverage area, financial aspects, vehicle settings, and integration of carsharing with other modes. Moreover, to understand the needs of service providers and public authorities, in-depth interviews were conducted. The results indicate that regulatory barriers, integration with other transport modes, and social equity issues are the most critical elements for the thriving of carsharing services. Our results also suggest that incentives can be divided into two main categories, namely direct and indirect incentives. With regards to direct incentives, parking stood out as the most important incentive. Among indirect incentives, those associated with the integration of carsharing with other transport services, were prominent. As part of the methodology, the results of the qualitative study are validated through a quantitative analysis. A bigger sample of the population answered an online survey, which was used to validate the list of potential incentives that can help aligning the goals of stakeholders and users. Highlights: Policy recommendations on how incentives can be used to support the decision making process. A list of potential user-directed and stakeholder-directed incentives. Incentives are classified into two different categories: direct and indirect. The paper analyses three cities ( Copenhagen - Denmark, Munich - Germany, and Tel Aviv-Yafo - Israel). The results of the qualitative study are validated through a quantitative analysis.